DIGITAL TECHNOLOGIES IN THE CONTENT OF EDUCATION OF RURAL SCHOOLCHILDREN - Zelenko, Natalia; Zelenko, Grigoriy (Revista Inclusiones, 2020)
The aim of the study is the transformation of the content and methods of technological education of rural schoolchildren, with the consideration being given to the directions of agricultural development and the development of digital technologies. The article substantiates the relevance of including digital technologies into the educational curriculum for rural schoolchildren and the search for optimal pedagogical technologies to better introduce them. The scientific novelty of the research lies in the analysis of digital and intellectual technologies, which made it possible to determine the main directions for the development of the content of technological education, as well as in the development and substantiation of organizational and methodological solutions. The obtained results can be used in the process of designing the content and methods of teaching rural schoolchildren.